The Relationship Between Employee Engagement and Employee Productivity: Based on empirical studies in South Africa - Anathi, Sokhetye; Rudnák, Ildikó (Acta Carolus Robertus, 2024)
This study evaluates local tourism in Iran, focusing on domestic travel. The initial analysis explores the broader roleIn our study we provide a literature review on the relationship between employee engagement and effectiveness, exploring recent human resource trends. We briefly introduce HR trends for the 21st century, such as sustainable and green corporate goals and leadership. We compare large South African companies such as Vodacom, Standard Bank, and Sibanye still Waters with world-renowned multinationals such as Unilever, Johnson & Johnson, and Samsung to identify and illustrate the parallelism of trends and similarities while pointing out local specificities that guarantee local success. The method chosen is not a retrospective exploration but a presentation of the most recent literature. Our aim was to project the engagement and productivity of South African employees.
Keywords: human resources; green human resource management; employees, green practices; sustainability